The natural history of iguanura geonomaeformis martius: a Malayan undergrowth palmlet - Kiew, Ruth (International Palm Society, 1972)
Iguanura Blume is a genus of arecoid palms endemic to the Malayan Archipelago. There are twelve species described from Malaya of which I. geonomaejormis Martius was the first to be described in 1845. The specific epithet is apposite, as Martius notes in Historia Naturalis Palmarum (1823-50) that these are "Palmae arundinaceae habitu geonomae." The geonomoid palms, however, are still much better known than their equivalent Malayan palmlets.